2014
DOI: 10.1371/journal.pone.0104915
|View full text |Cite
|
Sign up to set email alerts
|

Nowcasting the Spread of Chikungunya Virus in the Americas

Abstract: BackgroundIn December 2013, the first locally-acquired chikungunya virus (CHIKV) infections in the Americas were reported in the Caribbean. As of May 16, 55,992 cases had been reported and the outbreak was still spreading. Identification of newly affected locations is paramount to intervention activities, but challenging due to limitations of current data on the outbreak and on CHIKV transmission. We developed models to make probabilistic predictions of spread based on current data considering these limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
124
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(128 citation statements)
references
References 27 publications
2
124
1
1
Order By: Relevance
“…Exposed mosquitoes transition to the infectious class at a rate V , which is inversely proportional to the mean extrinsic latent period in the mosquito population (2). Susceptible, exposed, and infectious mosquitoes all die at a rate that is inversely proportional to the mosquito lifespan, µ V (70). The mosquito-to-human force of infection follows the usual mass-action law in each subpopulation whose linear extension varies from a few miles to about 50 miles depending on the population density and specific area of the world.…”
Section: Methodsmentioning
confidence: 99%
“…Exposed mosquitoes transition to the infectious class at a rate V , which is inversely proportional to the mean extrinsic latent period in the mosquito population (2). Susceptible, exposed, and infectious mosquitoes all die at a rate that is inversely proportional to the mosquito lifespan, µ V (70). The mosquito-to-human force of infection follows the usual mass-action law in each subpopulation whose linear extension varies from a few miles to about 50 miles depending on the population density and specific area of the world.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the ultimate outcome of alphaviral infection differs between vertebrate and invertebrate hosts, as infection of a vertebrate host results in acute cytolytic infection whereas infection of invertebrate hosts often results in persistent infection with minimal cell death (5-11). The widespread geographic distribution of competent vector mosquito species leading to contact with immunologically naive human populations has resulted in several significant outbreaks of alphaviral disease (12)(13)(14). Perhaps most notable is the ongoing reemergence of chikungunya virus, which caused significant morbidity during the height of the 2006 epidemic, with as many as 40,000 new cases per week (13).…”
mentioning
confidence: 99%
“…There were 22 no abnormalities in ZIKV-negative women [2]. Lastly, the complete ZIKV genome was 23 recovered from the brain of a fetus with microcephaly aborted by an expectant mother 24 infected during the 13 th week of gestation [7], and the CDC reported on two newborns 25 from Brazil with microcephaly who died shortly after birth and two miscarriages, all 26 tested positive for ZIKV [8]. In addition to the epidemiological evidence, newly 27 developed mouse models of ZIKV have demonstrated that ZIKV strains from French…”
mentioning
confidence: 99%
“…No official stance on delaying pregnancy has been 57 taken for unexposed women. Problematically, the public is receiving a mixed message, arboviruses vectored by Aedes aegypti (i.e., chikungunya virus, CHIKV) [22][23][24][25][26].…”
mentioning
confidence: 99%